Make America healthy again : how bad behavior and big government caused a trillion-dollar crisis - Saphier, Nicole (Broadside Books, an imprint of HarperCollinsPublishers, 2020)
"Memorial Sloan Kettering radiologist, nationally recognized patient advocate, and Fox News contributor Nicole Saphier argues that we can't fix the American healthcare system until we fix ourselves."--